Effect of WO3 Addition Process on V2O5/TiO2 Monolithic Catalysts - He, Yuanyuan; Liu, Qingcai; Yang, Jian; Xi, Wenchang (Asian Journal of Chemistry, 2013)
Selective catalytic reduction catalysts were prepared by introducing WO3 with ammonium metatungstate instead of WO3-TiO2 powders. The surface and redox properties of these catalysts were investigated by BET, XRD, FT-Raman, H2-TPR and catalytic activity test. The results showed that the catalyst prepared by new WO3 addition technology had a less surface area and a smaller pore volume. However it exhibited a superior activity and presented a wider activity temperature window. The interaction of vanadia and tungsta on the surface of support was more intensify and consequently led to more octahedrally coordinated vanadyl species formed and tetrahedral wolframyl species appeared. These should be the reasons for the excellent performance of catalyst with WO3 fed by ammonium metatungstate in mixed procedure.